18F‐Fluorodeoxyglycosylamines: Maillard reaction of 18F‐fluorodeoxyglucose with biological amines†. (11th December 2013) - Baranwal, Aparna; Patel, Himika H.; Mukherjee, Jogeshwar
<x xml:space="preserve">Abstract</x> The Maillard reaction of sugars and amines resulting in the formation of glycosylamines and Amadori products is of biological significance, for drug delivery, role in central nervous system, and other potential applications. We have examined the interaction of 18F‐fluorodeoxyglucose (18F‐FDG) with biological amines to study the formation of 18F‐fluorodeoxyglycosylamines (18F‐FDGly). Respective amines N‐allyl‐2‐aminomethylpyrrolidine (NAP) and 2‐(4′‐aminophenyl)‐6‐hydroxybenzothiazole (PIB precursor) were mixed with FDG to provide glycosylamines, FDGNAP and FDGBTA. Radiosynthesis using 18F‐FDG (2–5 mCi) was carried out to provide 18F‐FDGNAP and 18F‐FDGBTA. Binding of FDGBTA and 18F‐FDGBTA was evaluated in human brain sections of Alzheimer's disease (AD) patients and control subjects using autoradiography. Both FDGNAP and FDGBTA were isolated as stable products. Kinetics of 18F‐FDGNAP reaction indicated a significant product at 4 h (63% radiochemical yield). 18F‐FDGBTA was prepared in 57% yield. Preliminary studies of FDGBTA showed displacement of 3H‐PIB (reduced by 80%), and 18F‐FDGBTA indicated selective binding to Aβ‐amyloid plaques present in postmortem AD human brain, with a gray matter ratio of 3 between the AD patients and control subjects. We have demonstrated that 18F‐FDG couples with amines under mild conditions to form 18F‐FDGly in a manner similar to click chemistry. Although these amine derivatives are stable in vitro, stability in vivo and selective binding is under investigation. Copyright © 2013 John Wiley & Sons, Ltd.